Fetal monocytes possess increased metabolic capacity and replace primitive macrophages in tissue macrophage development. (2nd January 2020) - Li, Fengqi; Okreglicka, Katarzyna Maria; Pohlmeier, Lea Maria; Schneider, Christoph; Kopf, Manfred
Abstract: Tissue‐resident macrophages (MΦTR ) originate from at least two distinct waves of erythro‐myeloid progenitors (EMP) arising in the yolk sac (YS) at E7.5 and E8.5 with the latter going through a liver monocyte intermediate. The relative potential of these precursors in determining development and functional capacity of MΦTR remains unclear. Here, we studied development of alveolar macrophages (AM) after single and competitive transplantation of different precursors from YS, fetal liver, and fetal lung into neonatal Csf2ra −/− mice, which lack endogenous AM. Fetal monocytes, promoted by Myb, outcompeted primitive MΦ (pMΦ) in empty AM niches and preferentially developed to mature AM, which is associated with enhanced mitochondrial respiratory and glycolytic capacity and repression of the transcription factors c‐Maf and MafB. Interestingly, AM derived from pMΦ failed to efficiently clear alveolar proteinosis and protect from fatal lung failure following influenza virus infection. Thus, our data demonstrate superior developmental and functional capacity of fetal monocytes over pMΦ in AM development and underlying mechanisms explaining replacement of pMΦ in fetal tissues. Synopsis: This study demonstrates that fetal monocytes outcompete primitive macrophage (pMΦ) precursors in development of alveolar macrophages (AM) due to increased metabolic capacities. Moreover, fetal monocyte‐derived AM have superior functional capacities compared to pMΦ‐derived AM. Fetal monocytes have a superior capacity in AM development compared to primitive macrophages (pMΦ). Myb expression in fetal liver monocytes promotes AM development. Fetal monocytes display enhanced mitochondrial respiratory and glycolytic capacity and repression of the transcription factors c‐Maf and MafB compared to pMΦ. AM derived from pMΦ fail to efficiently clear alveolar proteinosis and protect from fatal lung failure following influenza virus infection. Abstract : Transplantation studies aiming to identify the origin of tissue alveolar macrophages implicate a contribution of fetal monocytes with higher mitochondrial bioenergetic and glycolytic capacity than primitive macrophages.